Comparison of TEM sample preparation methods for immunogold labeling - Grechhamer, Christian (Jihočeská univerzita, 2017)
The tracking of antigens in biological samples can be achieved by labeling them with gold-gonjugated antibodies (immunogold labeling). This thesis gives an overview of several sample preparation methods for TEM and investigates their effects on the binding efficiency of antibodies to certain antigens. For this reason, protein samples were processed according to four different protocols, cut into ultra-thin sections and labeled with primary and secondary antibodies. The micrographs, taken during observation with a TEM, were analysed quantitatively and the obtained data was statistically evaluated.
Comparison of TEM sample preparation methods for immunogold labeling
-
Keywords: Transmission Electron Microscopy; immunogold labeling; microwave-assisted sample preparation; high pressure freezing; super quick freeze substitution; microtomy; gold quantitation; labeling density; Transmission Electron Microscopy; immunogold labeling; microwave-assisted sample preparation; high pressure freezing; super quick freeze substitution; microtomy; gold quantitation; labeling density